AB017. Basic research progress in microenergy medicine - Xin, Zhongcheng (Transl Androl Urol, 2016)
In the last decade, the convergence of life sciences, physical sciences, and engineering has brought a host of opportunities and innovations for biomedical informatics and health care in microenergy medicine, and it is called the third revolution in the field of life science research. Low-energy shock wave therapy (LESWT), a form of physical therapy in energy medicine, was shown to markedly improve erectile function in patients with organic ED, as well as in diabetic rats. In addition, LESWT has been demonstrated to facilitate elongation of myelinated axons, with consequent neurologic functional recovery in a rat model. Low-intensity pulsed ultrasound (LIPUS) is a form of ultrasound that delivered at a much lower intensity than traditional ultrasound energy and output in the mode of pulse wave. LIPUS have been demonstrated to have a rage of biological effects on tissues, including promoting bone-fracture healing, accelerating soft-tissue regeneration, inhibiting inflammatory responses and so on. Recent studies showed that biological effects of LIPUS in healing morbid body tissues may be mainly associated with the upregulation of cell proliferation and promoting multilineage differentiation of mesenchyme stem/progenitor cell lines. Therapeutic magnetic field, a good paradigm of convergence medicine, has been demonstrated to have beneficial results in benign prostatic hyperplasia (BPH), human breast carcinoma, peripheral nerve regeneration, hand osteoarthritis, osteonecrosis, and nucleic acid delivery. Magnetic field has been proven to be a safe, non-invasive method for numerous cell and tissue modifications, especially in musculoskeletal system.